Antibacterial Edible Coating of Ipomea batatas Incorporated with Lactobacillus acidophilus - Miksusanti miksusanti; Najmatul Asriah; Indah Solihah; Dina Permata Wijaya (RAFFLESIA JOURNAL OF NATURAL AND APPLIED SCIENCES, 2022)
This study was conducted to analyze the effect of variations concentration of Lactobacillus acidophilus in edible coatings and their antibacterial activity against E. coli using the well diffusion method. This study used an edible coating of Prebiotic from purple sweet potato starch and Lactobacillus acidophilus with dilution variations (10-6, 10-7, 10-8, 10-9) as probiotics. In this study physical properties were tested for edible coatings such as color tests with visual observations, water content by the gravimetric method and viscosity using Viscometer Ostwald. The content of organic acids in edible coating solutions was measured using the HPLC method. Organoleptic test was conducted with taste and color parameters on the A-E scale of 30 respondents. Research results showed edible coating discoloration before and after incorporation from deep purple to brown. The value of water content and viscosity also changed from 62,8% to 71,4% and 569,97 cp to 486,64 cp respectively. The best antibacterial activity of edible coating incorporation with Lactobacillus acidophilus was 263,76 mm2. Organoleptic test on grapes that have been coated with edible coating showed that covered with edible coating contains probiotics (Lactobacillus acidophilus) has no effect on respondents' perception. Lactic acid and acetic acid were exist in edible coating which were incorporated with Lactobacillus acidophilus.